PENGEMBANGAN MEDIA PEMBELAJARAN E-BOOK BERBANTUAN APLIKASI BOOK CREATOR ADA MATERI TEKS NARASI KELAS III SD NEGERI 1 POMAH - Avivah, Shinta Nur (Nindikayla Institute, 2023)
Development of E-Book Media based on the Book Creator Application is designed taking into account the needs of teachers and students. This media was developed to provide learning resources for Indonesian language subjects in Class III of SD N 1 Pomah. E-book media was developed in the Book Creator application with Narrative Text material. This research aims to: (1) develop e-book media based on the Book Creator Application, (2) test the feasibility of e-book media based on the Book Creator Application. This research uses the Borg and Gall model with five research steps, namely; potential and problems, data/information collection, product design, design validation, design revision. E-book media is designed using the Canva application, which accesses the media using a link connected to the internet. The results of the e-book media feasibility test that have been tested by media experts and material experts get the